2021
DOI: 10.3389/fmolb.2020.608447
|View full text |Cite
|
Sign up to set email alerts
|

CYP11A1 Upregulation Leads to Trophoblast Oxidative Stress and Fetal Neurodevelopmental Toxicity That can be Rescued by Vitamin D

Abstract: During normal pregnancy, the placental trophoblast secretes a variety of steroid hormones and participates in the regulation of maternal physiological functions and fetal development. The CYP11A1 gene encodes the cholesterol side-chain cleavage enzyme P450scc, which catalyzes the production of pregnenolone from cholesterol, which is the first step in the synthesis of all steroid hormones. Under the influence of genetic susceptibility and certain environmental factors, such as drugs and toxins, the expression o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 53 publications
0
5
0
Order By: Relevance
“…However, the molecular mechanisms underlying the anticancer effects of CYP11A1 on RCC are largely unknown. CYP11A1 reportedly triggers excessive oxidative stress in mitochondria against a human placental cell line derived from choriocarcinoma [ 19 ].…”
Section: Discussionmentioning
confidence: 99%
“…However, the molecular mechanisms underlying the anticancer effects of CYP11A1 on RCC are largely unknown. CYP11A1 reportedly triggers excessive oxidative stress in mitochondria against a human placental cell line derived from choriocarcinoma [ 19 ].…”
Section: Discussionmentioning
confidence: 99%
“…Overexpression of CYP11A1 increases ROS levels, as previously shown in our studies [ 14 ]. Moreover, excessive biosynthesis of CYP11A1 in mitochondria also leads to lipid peroxidation in BeWo cells [ 20 ]. In cellular membranes, lipid peroxidation is mainly responsible for ferroptosis, an iron-dependent cell death process [ 21 ].…”
Section: Resultsmentioning
confidence: 99%
“…The upregulated CYP11A1 in placentas might suggest over‐oxygen consumption and oxidative stress. In the BeWo cell line, upregulation of CYP11A1 induced excessive mitochondrial oxidative stress 45 . In addition, CYP11A1 inhibited cell proliferation and induced apoptosis in extravillous trophoblast cells 46 .…”
Section: Discussionmentioning
confidence: 98%
“…In the BeWo cell line, upregulation of CYP11A1 induced excessive mitochondrial oxidative stress. 45 In addition, CYP11A1 inhibited cell proliferation and induced apoptosis in extravillous trophoblast cells. 46 However, another study of cadmium exposure-induced FGR identified that CYP11A1 expression and progesterone synthesis were reduced in the mice models as well as in human placentas of small for gestational age.…”
Section: Genesmentioning
confidence: 99%